Elastic Load-Deflection Behavior of Timber Laminated Beam on Flexural Test - Fengky S Yoresta (Jurnal Ilmu dan Teknologi Kayu Tropis, 2015)
This research aims to understand the behavior of elastic bending curve on several types of timber laminated beams using bolts and combination of bolt-adhesive as connector among the timber layers. The beams are divided into types A, B, and C based on position of bolts and adhesive on beam. Flexural testing is conducted with one-point loading method using 5 tons capacity of Instron machine. The test results are then compared with theory of beam deflection by Euler-Bernoulli and Timoshenko. The research concludes that Timoshenko beam equation is accurate enough to predict the elastic behavior of beams. Deflection obtained from experiment is about two times larger than Euler-Bernoulli beam and not more than 1% error to Timoshenko.Keywords: adhesive, bolts, elastic behavior, flexural testing, laminated beam